The Protective Effect of Quercetin on Endothelial Cells Injured by Hypoxia and Reoxygenation - Li, Meng-Ting; Ke, Jia; Guo, Shu-Fen; Wu, Yang; Bian, Yue-Feng; Shan, Li-Li; Liu, Qian-Yun; Huo, Ya-Jing; Guo, Cen; Liu, Ming-Yuan; Liu, Ya-Jie; Han, Yan (Frontiers in Pharmacology, 2021)
Background: Cerebral small vessel disease (CSVD) is a group of clinical syndromes covering all pathological processes of small vessels in the brain, which can cause stroke and serious dementia. However, as the pathogenesis of CSVD is not clear, so the treatment is limited. Endothelial cell dysfunction is earlier than clinical symptoms, such as hypertension and leukosis. Therefore, the treatment of endothelial cells is expected to be a new breakthrough. Quercetin, a flavonoid present in a variety of plants, has the function of anti-inflammation and anti-oxidation. This study aimed to investigate the protective effect of quercetin on endothelial cell injury and provide a basic theory for subsequent application in the clinic. Methods: Human brain microvascular endothelial cells (HBMECs) were cultured in vitro, and the injury model of endothelial cells was established by hypoxia and reoxygenation (H/R). The protective effects of quercetin on HBMECs were studied from the perspectives of cell viability, cell migration, angiogenesis and apoptosis. In order to further study the mechanism of quercetin, oxidative stress and endoplasmic reticulum stress were analyzed. What’s more, blood-brain barrier (BBB) integrity was also studied. Results: Quercetin can promote the viability, migration and angiogenesis of HBMECs, and inhibit the apoptosis. In addition, quercetin can also activate Keap1/Nrf2 signaling pathway, reduce ATF6/GRP78 protein expression. Further study showed that quercetin could increase the expression of Claudin-5 and Zonula occludens-1. Conclusions: Our experiments show that quercetin can protect HBMECs from H/R, which contains promoting cell proliferation, cell migration and angiogenesis, reducing mitochondrial membrane potential damage and inhibiting cell apoptosis. This may be related to its antioxidation and inhibition of endoplasmic reticulum stress. At the same time, quercetin can increase the level of BBB connexin, suggesting that quercetin can maintain BBB integrity.